A questão da colonização no Brasil: historiografia e documentos - Mendes, Claudinei Magno Magre [UNESP] (My University, 2012)
In this article we draw attention to the fact that the documentation relating to the decision to colonize Brazil, as well as the early stages of colonization, comprising two interpretations about the reasons to occupy, populate and organize the production on American soil. The Brazilian historiography joined the explanation of that pressure from European nations led to the Portuguese crown decided on an occupation more effectively. But without ignoring this reason, the documentation allows to take into account their own historical circumstances created by the development of trade. These are essential conditions for the emergence and effectiveness of the proposal to colonize Brazil. Thus, when considering only the pressure of European nations the Brazilian historiography remained on the surface of events. It’s necessary to take into account the documentation on what it allows to grasp the colonial process as a historical phenomenon and not just as an act of will.

Neste artigo, procuramos chamar a atenção para o fato de a documentação relativa à decisão de se colonizar o Brasil, bem como a das primeiras fases da colonização, comportarem duas interpretações quanto aos motivos de se ocupar, povoar e organizar a produção em terras americanas. A historiografia brasileira aderiu à explicação de que a pressão das nações europeias levou a Coroa portuguesa a decidir por uma ocupação mais efetiva. No entanto, sem desconsiderar este motivo, nós nos apoiamos na documentação para mostrar que é possível levar em conta as próprias circunstâncias históricas criadas pelo desenvolvimento do comércio. Tais condições foram imprescindíveis para o surgimento e efetivação da proposta de se colonizar o Brasil. Assim, ao considerar apenas a pressão das nações européias, a historiografia brasileira permaneceu na superfície dos fatos, sem levar em conta na documentação que é possível apreender o processo colonial como um fenômeno histórico e não apenas como ato de vontade.
The issue of colonization: historiography and documents
Keywords: Colonization; Brazilian historiography; Documents; Education history; História e Política; Historiografia; Debates políticos; Intelectuais; Escritos coloniais; História do Brasil colonial